Conducting a child injury prevention RCT in the wake of COVID-19: lessons learned for virtual human subjects research - Prokos, Sophia; Damashek, Amy; Morrongiello, Barbara; Arbour, Emilie; Belachew, Bethelhem; Zafreen, Farzana (Frontiers in Digital Health, 2023)
Unintentional injury is the leading cause of death among children in the United States, and children living in low-income households are particularly at risk for sustaining unintentional injuries. Close parental supervision has been found to reduce young children's risk for injury; however, few studies have examined interventions to increase parental supervision. This paper discusses COVID-19 related modifications that were made to a federally funded randomized controlled trial to reduce low-income children's risk for unintentional injury. The study's procedures (data collection and intervention delivery) had to be transitioned from in-person to a fully virtual format. Modifications that were made to the study included use of: participant cell phones to conduct data collection and intervention sessions; virtual meeting software to conduct sessions with participants and; an online platform to collect questionnaire data. In addition, many modifications were required to complete the in-home observation virtually. In terms of feasibility, the investigators were able to collect all of the data that was originally proposed; however, recruitment and retention was more challenging than anticipated. Lessons learned during the modification process are included to provide guidance to researchers seeking to conduct virtual human subjects research in the future.